In-depth review 2024 (Publications Office of the European Union, 2024)
This in-depth review (IDR) analyses the evolution of France's vulnerabilities related to high government debt and competitiveness, in a context of low productivity growth, which carry cross-border relevance, and possibly newly emerging risks. This year's IDR, which follows the 2024 Alert Mechanism Report (AMR) published in November 2023, assesses the persistence or unwinding of the vulnerabilities identified last year, potential emerging risks, and relevant policy progress and policy options that could be considered for the future. Given the size of the French economy and its interlinkages with the other Member States, these vulnerabilities have a cross-border relevance.
10.2765/0093
Keywords: Graue Literatur; macroeconomics; euro area; loan; financial stability; financial supervision; household consumption; gross domestic product; inflation; competitiveness; economic growth; labour market; economic recovery; France